Responding to the call: Arts methodologies informing 21st century literacies - Huber, A.; Dinham, Judith; Chalk, Beryl (Blackwell Publishing Ltd, 2015)
© 2015 UKLA. With the advent of digital technologies, a new adventure began. How the world works has changed, and we cannot go back. Digitally savvy children born in the digital age (i.e., DigiKids) are interacting with and responding to rich, curatable multimodal communications as part of their daily-lived experience. For DigiKids, traditional text-based literacy is of diminishing significance as they exercise a wide range of new literacy practices and capacities. Having more the mindset of the artist, they engage in the world of expression and communication, weaving together linguistic, visual, aural, gestural and spatial features to form coherent compositions. Nevertheless, national curriculæ reformers, teachers and parents generally fear neglecting traditional text-based literacy skills and consequently struggle to optimise DigiKids' digitally savvy literacy practices and capacities. However, practices employed in arts methodologies (e.g. ceramics, theatre, and music) offer a key resource to conceptualise new practices beyond traditional text-based literacy, and to situate our new post-literacy (i.e. epiliteracy) theory. To navigate the transition from traditional text-based literacy to epiliteracy, the metaphor of the archetypal Hero/Heroine's Journey is used to describe, chart and comprehend the tensions, trials and transformations as we respond to the call of epiliteracy in the 21st century.